PENGARUH PERMAINAN KLASIFIKASI BERDASARKAN BENTUK TERHADAP KEMAMPUAN BERPIKIR SIMBOLIK PADA ANAK USIA 5-6 TAHUN DI TK BHAKTI IBU MARPOYAN DAMAI PEKANBARU - Mariana, Ides; Chairilsyah, Daviq; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :This study aims to determine determine the effect of classification game based on form on the ability of symbolic thinking in children aged 5-6 years In TK Bhakti Ibu Marpoyan Damai Pekanbaru. The population in this study that children B1 classes totaling 20 children and sample in this study amounted to 20 children. The method used pre-experimental design with one group pretest posttest design that experiments conducted on one group alone with no comparison group. This type of instrument used in this study is to use the observation and documentation to take notes about events that occurred during the treatment given. Based on the results obtained by testing the hypothesis that there are significant the effect of classification game based on form on the ability of symbolic thinking in children aged 5-6 years In TK Bhakti Ibu Marpoyan Damai Pekanbaru. This known t count 7,249 or significance (0.000), because sig < 0.05, it can be concluded that there are differences in the ability to know the symbolic thinking on students significant before and after using classification game. Based on the results obtained wilcoxon test there is the influence of classification based on shape on the ability of symbolic thinking in children aged 5-6 years In TK Bhakti Ibu Marpoyan Damai Pekanbaru.Keywords: Symbolic Thinking, Classification Based on Shape Game